Molecular relationship of chromosomal genes encoding biphenyl/polychlorinated biphenyl catabolism: some soil bacteria possess a highly conserved bph operon. - Furukawa, K (1989)
All the genes we examined that encoded biphenyl/polychlorinated biphenyl (PCB) degradation were chromosomal, unlike many other degradation-encoding genes, which are plasmid borne. The molecular relationship of genes coding for biphenyl/PCB catabolism in various biphenyl/PCB-degrading Pseudomonas, Achromobacter, Alcaligenes, Moraxella, and Arthrobacter strains was investigated. Among 15 strains tested, 5 Pseudomonas strains and one Alcaligenes strain possessed the bphABC gene cluster on the XhoI 7.2-kilobase fragment corresponding to that of Pseudomonas pseudoalcaligenes KF707. More importantly, the restriction profiles of these XhoI 7.2-kilobase fragments containing bphABC genes were very similar, if not identical, despite the dissimilarity of the flanking chromosomal regions. Three other strains also possessed bphABC genes homologous with those of KF707, and five other strains showed weak or no significant genetic homology with bphABC of KF707. The immunological cross-reactivity of 2,3-dihydroxybiphenyl dioxygenases from various strains corresponded well to the DNA homology. On the other hand, the bphC gene of another PCB-degrading strain, Pseudomonas paucimobilis Q1, lacked genetic as well as immunological homology with any of the other 15 biphenyl/PCB degraders tested. The existence of the nearly identical chromosomal genes among various strains may suggest that a segment containing the bphABC genes has a mechanism for transferring the gene from one strain to another.